A Positive Newborn Screen for Congenital Hypothyroidism in a Clinically Euthyroid Neonate-Avoiding Unnecessary Treatment - Ashleigh Brown; Paul Hofman; Bobby Li; Campbell Heron; Natasha Heather (MDPI AG, 2023)
Newborn screening for congenital hypothyroidism (CH) has dramatically improved the neurocognitive outcomes for newborns with a confirmed positive screening test result. However, screening yields a small number of false positive and false negative results. This report describes the first known case of familial dysalbuminaemic hyperthyroxinaemia presenting with a positive newborn thyroid stimulating hormone screen. This condition is characterized by artefactually elevated free tetraiodothyronine (T4) and triiodothyronine (T3) levels due to increased albumin binding and subsequent dissociation during laboratory assays but normal true free thyroid hormone and thyroid stimulating hormone (TSH) levels in a clinically euthyroid subject. This highlights the need to take care when attributing clinical significance to discordant results.